Hydrodynamic Aspects at Vitória Bay Mouth, ES - GARONCE,FLÁVIA A.A. (2014)
Understading the hydrodynamic behavior and suspended particulated matter (SPM) transport are of great importance in port regions such as Vitória Harbor, which is located at Vitória Bay, Vitória – ES, Brazil. Vitória Bay is an estuary that has not been systematically assessed through a temporal analysis in order to identify its hydrodynamics characteristics and SPM exchange. This study aims to investigate salt and suspended particulate matter flux at the estuarine mouth of Vitória Bay by understanding the temporal variation of salinity, temperature and tidal currents within the water column and at the channel crosssection. Results showed that the estuarine mouth tended to present partial stratification periods during neap tides and little stratification in spring tides. The circulation pattern was mainly influenced by the tide, with little influence from river discharge. With regard to the SPM, the mouth of the estuary tended to show low concentrations, with the highest values occurring during the dry season. A close relationship between momentary discharge, SPM and salt fluxes was observed. Despite all the data was collected at the mouth of the estuary, the system showed an importation trend of salt in all cycles and SPM importation for three of the four studied tidal cycles. Thus, Vitoria Bay is not exporting SPM to the adjacent inner shelf.